DEVELOPMENT OF BLOCKCHAIN-BASED 33KV/11KV SUBSTATION WITH OPERATING PRINCIPLES - SOPHEANIE SENIA, SIMON (Universiti Malaysia Sarawak (UNIMAS), 2022)
The purposed blockchain-based technology framework for the 33kV/11kV substation is to introduce the blockchain-based system to provide the working principle when working on the substation system. The blockchain-based technology is used to decentralize the system during the transaction of data in the substation. This is to ensure that the 33kV/11kV substation is safe from cyber-attacked issues. In this project, the research on the development of blockchain-based 33kV/11kV substation operating principles is investigated. The problem with this blockchain-based the improvement of the operating principle and the complexity of the blockchain-based technology. This project is about the development of the blockchain-based and how to apply the blockchain in the 33kV/11kV substation which includes the architecture of the blockchain-based operating principles. The general framework of blockchain-based technology in the methodology is proposed. In this project, the MATLAB simulation is used to design the 33kV/11kV substation. The application of Thing-Speak is used as a Phasor Data Concentrator (PDC) to collect the data from the Phasor Measurement Units (PMUs) in the simulation of the 33kV/11kV substation. This method is used to produce the blockchain as an authentication for the second party to access the data in the system. The blockchain is created in the form of code obtained by using Python programming language. The results of the system are used to protect the data in the substation from being attacked. The transaction of data that occurred in the system must be safe from cyber-attack issues.